Monetary stabilisation in a currency union of small open economies - Marcelo Sánchez (European Central Bank (ECB), 2008)
This paper studies stabilisation policies in a multi-country currency union of small open economies. It abstracts from key factors favouring currency union formation, such as reduced transaction costs and enhanced credibility, which are exogenous to the factors studied here. Demand-side shocks hamper monetary union stabilisation unless members face identical output-inflation tradeoffs and their business cycles are perfectly synchronised. Under supply shocks, welfare implications from joining a currency union are less clear cut. In particular, when these shocks are common across participating countries a tradeoff arises whereby the latter benefit if they are relatively open but are at a disadvantage in case they are of small size. Monetary-fiscal interaction leads to a free rider problem, with area-wide supply shocks eliciting higher interest rate variability. Compared with the case of real wage rigidity, increased real wage flexibility mitigates the free rider problem. Higher trade union decentralisation overall favours a currency union. The present multi-country currency union setup should not be seen as an attempt at settling the sharp differences that exist in the literature. Our model could be modified in order to derive results that are valid in more realistic environments. These include the analysis of public debt considerations in the case of fiscal policies, and both institutional and (further) macroeconomic aspects in the area of wage determination.
Keywords: E52; E58; F33; F42; E63; 330; Fiscal Policy; Montary union; small open economies; stabilisation; Wage setting; Welfare; Währungsunion; Inflationsbekämpfung; Stabilisierungspolitik; Finanzpolitik; Kleine offene Volkswirtschaft; Trittbrettfahrerverhalten; Konjunkturzusammenhang; Theorie